A checklist of digenean parasites (Platyhelminthes: Digenea) infecting molluscs and fishes in Portuguese waters (Northeast Atlantic) - Costa, G. (2017)
The present work is a compilation of the digenean parasites infecting molluscs (gastropods and bivalves), crabs and fishes of the Atlantic coast of Portugal and the Archipelagos of Azores and Madeira, based on literature sources, including research conducted by the present authors. A total of 65 digenea taxa were found, belonging to 24 families, infecting gastropods, bivalves, shore crabs and fishes. The most representative families of digeneans were the Hemiuridae (11 taxa), followed by the Bucephalidae (5 taxa), Opecoelidae (5 taxa) and the Zoogonidae (5 taxa). Hosts, site of infection, sampling locality and life cycle strategy are given when available. Further fields of research on the digenean parasites are suggested.